Discordance among Belief, Practice, and the Literature in Infection Prevention in the NICU - Hossam S. Alslaim; Jonathan Chan; Fozia Saleem-Rasheed; Yousef Ibrahim; Patrick Karabon; Nathan Novotny (Children, 2022)
This study evaluates practices of infection control in the NICU as compared with the available literature. We aimed to assess providers’ awareness of their institutional policies, how strongly they believed in those policies, the correlation between institution size and policies adopted, years of experience and belief in a policy’s efficacy, and methods employed in the existing literature. An IRB-approved survey was distributed to members of the AAP Neonatal Section. A systematic review of the literature provided the domains of the survey questions. Data was analyzed as appropriate. A total of 364 providers responded. While larger NICUs were more likely to have policies, their providers are less likely to know them. When a policy is in place and it is known, providers believe in the effectiveness of that policy suggesting consensus or, at its worst, groupthink. Ultimately, practice across the US is non-uniform and policies are not always consistent with best available literature. The strength of available literature is adequate enough to provide grade B recommendations in many aspects of infection prevention. A more standardized approach to infection prevention in the NICU would be beneficial and is needed.